The use of the back distribution route to detect the sources of dust storm - Khadim , Ali; Atia, Ali (Iraqi Journal of Science, 2024)
The use of the remote sensing techniques give a good results in detection of the sources of dust storm. The results reflect that the dust concentration decreases away from their sources and it is possible to find the equation between the dust concentration and the straight vistion.